The Enterprise Lingua Franca: A Foundational Framework for Semantic Interoperability and Cross-Functional Cognition - Simon Suwanzy Dzreke; Semefa Elikplim Dzreke (Sultan Publisher, 2026)
Digital transformation often fails at the conceptual level: Seventy-three percent of cross-functional initiatives fail because the functional mental models don't match up, making it impossible to solve difficult problems like making sustainability profitable. This research identifies a significant deficiency in enterprise interoperability, wherein disparate departmental epistemologies manifested in conflicting interpretations of fundamental constructs such as